2018
DOI: 10.1016/j.stemcr.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Adult Human Pancreatic Tissue Yields Organoids Harboring Progenitor Cells with Endocrine Differentiation Potential

Abstract: SummaryGenerating an unlimited source of human insulin-producing cells is a prerequisite to advance β cell replacement therapy for diabetes. Here, we describe a 3D culture system that supports the expansion of adult human pancreatic tissue and the generation of a cell subpopulation with progenitor characteristics. These cells display high aldehyde dehydrogenase activity (ALDHhi), express pancreatic progenitors markers (PDX1, PTF1A, CPA1, and MYC), and can form new organoids in contrast to ALDHlo cells. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
129
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 52 publications
1
129
0
Order By: Relevance
“…In the characterization of hPOs, the authors reported the presence of ductal cells and ductal progenitors but differentiation into endocrine cells producing insulin was not demonstrated in this work. Remarkably, viability rates were always above 75% after thawing thus demonstrating the feasibility of generating a bank of cryopreserved organoids, which could be further differentiated, either in vitro or in vivo, into insulin-producing cells, as already shown to be feasible by other authors [15]. This is a key point that will need to be addressed next to ensure clinical success, provided that the potency of hPO generated in this work will rely on their capacity to generate insulin and restore normoglycemia.…”
Section: Introductionsupporting
confidence: 64%
“…In the characterization of hPOs, the authors reported the presence of ductal cells and ductal progenitors but differentiation into endocrine cells producing insulin was not demonstrated in this work. Remarkably, viability rates were always above 75% after thawing thus demonstrating the feasibility of generating a bank of cryopreserved organoids, which could be further differentiated, either in vitro or in vivo, into insulin-producing cells, as already shown to be feasible by other authors [15]. This is a key point that will need to be addressed next to ensure clinical success, provided that the potency of hPO generated in this work will rely on their capacity to generate insulin and restore normoglycemia.…”
Section: Introductionsupporting
confidence: 64%
“…Organoids are an important bridge between two-dimensional cultures and in vivo models because they are more physiologically relevant than monolayer cell culture models while being far more amenable to manipulation of niche components, signaling pathways, and genome editing than in vivo models [1]. Since 2009, many protocols have been implemented for the culture of organoids isolated from various tissues, such as liver [2][3][4][5], pancreas [6][7][8], lung [9], gut [10][11][12], stomach [13,14], and prostate [15]. Consequently, organoids can provide excellent model systems for a wide range of basic research studies, including expression profiling studies and analyses of rare cell lineages that are difficult to access in vivo [16].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, undifferentiated hPOs recapitulate the phenotype of pancreas ductal epithelia in vitro, with a hollow spherical polarized cell monolayer enclosing a central lumen [23]. Furthermore, they can be cultured, expanded, and differentiated into endocrine lineage cells in vivo and in vitro [8,23]. Currently, hPOs can be generated from primary pancreas tissue [3] or induced pluripotent stem cells [24].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this obstacle, in recent years, the development of in vitro organoids as a 3D culture system has gained attention as a model to study different tissues (Dorrell et al., ; Grapin‐Botton, ; Hattori, ; Hindley & Cordero‐Espinoza, ; Hohwieler et al., ; Jackson & Lu, ; Jin et al., ; Lancaster & Knoblich, ; Li et al., ; Loomans et al., ; Oshima, Ogawa, & Tsuji, ; Sato et al., ; Shamir & Ewald, ; Wills & Drenth, ; Xia et al., ; Xu, Tong, & Ran, ). With this method, isolated cells are suspended in matrices that are suitable to provide extracellular interactions, allowing the cells to grow in a 3D format.…”
Section: Introductionmentioning
confidence: 99%
“…With this method, isolated cells are suspended in matrices that are suitable to provide extracellular interactions, allowing the cells to grow in a 3D format. Culturing isolated cells in a defined 3D environment has been an informative approach to dissect the complex nature of cells in a simple model (Boj et al., ; Dorrell et al., ; Loomans et al., ; Shamir & Ewald, ).…”
Section: Introductionmentioning
confidence: 99%